A Pilot Study on the Association of the Upayoga samstha- Ashta Ahara Vidhi Visheshayatana Questionnaire (US-AAVVQ) with Glycemic Status and Indian Diabetic Risk Score (IDRS) in an Adult Population - Dr. Saurabh Agrawal; Dr. Aparna Bagul; Dr. Asha K.P (The Bioscan, 2025)
Background: Diabetes mellitus poses a major health challenge in India. While the Indian Diabetic Risk Score (IDRS) is valuable for risk identification, comprehensive lifestyle and dietary assessments can provide crucial additional insights. Objective: This pilot study aimed to evaluate the novel Upayoga samstha- Ashta Ahara Vidhi Visheshayatana Questionnaire (US-AAVVQ) among healthy, pre-diabetic, and diabetic individuals; compare US-AAVVQ responses with IDRS; and analyze response variations by glycemic category, age, and sex. Methods: A cross-sectional survey involved 170 adults (35-65 years) from Sanjeevani Ayurveda Hospital OPD and village camps in Jodhpur. Participants, categorized by Fasting Blood Sugar (FBS) per ICMR 2018 guidelines, completed the 55-item US-AAVVQ (assessing dietary habits, eating behaviors, meal experiences) and IDRS components via Google Forms. Results: Higher IDRS scores strongly correlated with pre-diabetic and diabetic status. The US-AAVVQ effectively differentiated glycemic groups: healthy individuals reported significantly more positive habits (e.g., "Always" fresh food, "Never" post-meal discomfort) compared to pre-diabetic (intermediate responses) and diabetic individuals (less favorable habits). While IDRS components varied by age/sex as expected, US-AAVVQ response variations by age/sex were not prominent after glycemic stratification within the 35-65 age group. Discussion & Conclusion: The US-AAVVQ demonstrates potential in differentiating individuals by glycemic status, aligning with IDRS. It offers granular insights into specific modifiable behaviors, complementing IDRS. This pilot study suggests US-AAVVQ could be a useful tool for assessing diabetes-related lifestyle factors in this Jodhpur population, but further validation in larger, diverse samples is essential to confirm its broader utility.